2016
DOI: 10.7326/m15-0919
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Patients With Recent-Onset Rheumatoid Arthritis After 10 Years of Tight Controlled Treatment

Abstract: Dutch College of Health Insurance Companies, Schering-Plough, and Janssen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 35 publications
4
83
1
Order By: Relevance
“…Better control of RA activity has recently been associated with fewer cardiovascular events [13]. Treat-to-target is the new gold standard for achieving RA control which has been shown to improve numerous outcomes [14] in randomized controlled trials [1517]. “Abrogation of inflammation” by controlling RA, as emphasized in the 2014 treat-to-target update, improves CVD risk given the association between chronic inflammation and CVD [10].…”
Section: Introductionmentioning
confidence: 99%
“…Better control of RA activity has recently been associated with fewer cardiovascular events [13]. Treat-to-target is the new gold standard for achieving RA control which has been shown to improve numerous outcomes [14] in randomized controlled trials [1517]. “Abrogation of inflammation” by controlling RA, as emphasized in the 2014 treat-to-target update, improves CVD risk given the association between chronic inflammation and CVD [10].…”
Section: Introductionmentioning
confidence: 99%
“…While evidence has continued to accumulate demonstrating that a T2T strategy in RA reduces morbidity and mortality, implementation in routine clinical practice remains challenging . There are many and varied barriers to the implementation of RA T2T and these may include funding models, waiting lists, public versus private pathways, cost of care including pharmaceuticals and patient factors including education level, health literacy, multifaceted adherence issues and rheumatology service access.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the results of the current trial are far superior. To our knowledge, studies with an active, modern treat‐to‐target strategy and long follow‐up times are sparse . The Dutch Behandel Strategieen (BeSt) trial compared 4 strategies guided by the DAS in 508 patients with early RA .…”
Section: Discussionmentioning
confidence: 99%
“…There are few trials using the modern treat‐to‐target approach with truly long‐term follow‐ups (at least 10 years), or comprehensive follow‐up coverage . Our previous analyses of the study TNF‐Blocking Therapy in Combination With Disease‐Modifying Antirheumatic Drugs in Early Rheumatoid Arthritis (NEO‐RACo) have shown that in early RA, an intensified initial combination treatment strategy (Finnish Rheumatoid Arthritis Combination Therapy Trial [FIN‐RACo]) with methotrexate (MTX), sulfasalazine, hydroxychloroquine, and low‐dose 7.5‐mg prednisolone for 2 years, and free, active, remission‐targeted DMARD treatment thereafter, resulted in very low disease activity in most patients at 2 and 5 years.…”
Section: Introductionmentioning
confidence: 99%